PENGARUH TEKNIK MIND MAPPING BERBASIS PjBL TERHADAP KETERAMPILAN MEMPRODUKSI TEKS LAPORAN HARIL OBSERVASI SISWA KELAS X SMA EKASAKTI PADANG - Zuraida Khairani (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
The purpose of this research is three things. First, describe the skills of producing statement observation text of SMA Ekasakti Padang student of before applied technic Mind Mapping of based of Project based Learning Model. Second, describe the skill of producing statement observation text of SMA Ekasakti Padang student after applied technic Mind Mapping based of Project based Learning Model. Third, analyze the influence of thetechnic Mind Mapping based of Project based Learning Model to the skill of producing statement observation text of grade X students of SMA Ekasakti Padang. This type of research is quantitative research. The research method applied is descriptive method of analysis. Based on the results of data analysis and discussion obtained the following conclusions. First, the skill of producing the statement observation text of the students of class X IPA 1 SMA Ekasakti Padang before applied the technic Mind Mapping based on the model of Project based Learning is in medium qualification with the average value of 64. Second, the skill of producing the statement observation text of the students of class X IPA 1 SMA Ekasakti Padang after the adoption technic Mind Mapping method Based on the Project based Learning model is in good qualification with the average value of 84. Third, the influence of the application of technic Mind Mapping method Based on the Project based Learning model on the skills of producing poetical text after the t-test at the level of 0.95, obtained tcount> ttable or 9.42> 1.70. So H0 is rejected and H1 accepted. This means, the implementation of technic Min Mapping method Based on the Project based Learning model is feasible applied to learning to produce statement observation text of students of class X SMA Ekasakti Padan